RELATIONSHIP BETWEEN GLOBAL CLIMATE CHANGE AND CARDIOVASCULAR DISEASE: ANALYSIS AND FORECASTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article discusses the relationship between global climate change and cardiovascular diseases. The mechanisms of climate change impact on the cardiovascular system, as well as statistical data confirming the increase in the number of diseases in the context of rising temperatures and air pollution are discussed from cardiovascular diseases. To combat these threats, a comprehensive approach is proposed, including the adaptation of medical systems and the improvement of public health.